Strategies of Formerly Incarcerated Balinese Women in Fighting Social Stigma - Narawati, Made; A. Rosenbaum, Stephen; Beratha, Ni Luh Sutjiati; Suarka, I Nyoman; Kusuma, I Nyoman Weda; Putra, I Nyoman Darma (Udayana Journal of Law and Culture, 2025)
As in other regions of Indonesia, after serving their prison sentences, many women in Bali face difficulties in re-integrating into society. This article aims to reveal the strategies employed by formerly incarcerated Balinese females in combating social stigma. The chosen cases include embezzlement, identity fraud, and drug-related offenses, with the intention of understanding the challenges faced by these women. Data were collected through observation and interviews, focusing on the strategies utilized by three women to fight stigma and the legal perspectives regarding their stigmatization of these women. The analysis concludes that the patriarchal culture extends the arena of stigmatization for former Balinese female prisoners, as they have lost certain rights within their families and traditional socio-cultural norms. Stigma presents challenges for them in leading a normal life and hinders their social reintegration. Certain legal provisions reinforce this stigma, leading to discriminatory effects. This article encourages communities of former friends to participate in supporting them, so they become aware and do not reoffend. In this context, the role of the government and customary institutions is crucial in assisting former prisoners to return to normal societal life. Specifically , the BAPAS , the institution which, under Indonesian law, carries out the function of community guidance, plays an active part in accompanying former prisoners to ensure they regain their full rights as citizens.